2005
DOI: 10.1210/jc.2004-0263
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Obese Adolescents with Sibutramine: A Randomized, Double-Blind, Controlled Study

Abstract: Adolescent obesity is becoming a health problem in both developed and developing countries. Antiobesity drug therapy is not currently indicated for the treatment of adolescent obesity and remains investigational at this time. The aim of this study was to determine the efficacy and safety of sibutramine in obese adolescents. A randomized, double-blind, placebo-controlled trial, enrolling 60 adolescents, aged 14-17 yr, for 6 months was conducted. In the first month, all patients received placebo and a hypocalori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(80 citation statements)
references
References 19 publications
2
73
0
4
Order By: Relevance
“…14 However, in a recent study in obese adolescents treated with sibutramine, similar to our findings, a slight decrease in both blood pressure as well as heart rate was noted. 49 Currently, there is no similar explanation for the small fall in mean heart rate seen in this study. In patients with uncomplicated obesity, treatment with Short-term therapy with sibutramine Z Gaciong and G Placha sibutramine has been reported to be associated with a dose-dependent increase in heart rate with an overall mean increase of 3-7 bpm.…”
Section: Discussionmentioning
confidence: 57%
“…14 However, in a recent study in obese adolescents treated with sibutramine, similar to our findings, a slight decrease in both blood pressure as well as heart rate was noted. 49 Currently, there is no similar explanation for the small fall in mean heart rate seen in this study. In patients with uncomplicated obesity, treatment with Short-term therapy with sibutramine Z Gaciong and G Placha sibutramine has been reported to be associated with a dose-dependent increase in heart rate with an overall mean increase of 3-7 bpm.…”
Section: Discussionmentioning
confidence: 57%
“…Similarly for sibutramine, published studies report that this drug is generally well tolerated in adolescents [21][22][23]. The largest trial, a randomized placebo-controlled trial in 498 obese adolescents over 12 months, reported that 76% of those in the sibutramine arm continued the drug for the full 12-month trial period, with only 6% of subjects withdrawing because of adverse events [22].…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…The largest trial, a randomized placebo-controlled trial in 498 obese adolescents over 12 months, reported that 76% of those in the sibutramine arm continued the drug for the full 12-month trial period, with only 6% of subjects withdrawing because of adverse events [22]. In a smaller randomized controlled trial of 60 obese adolescents over 6 months, 93% completed the 6-month trial and no subjects withdrew due to sibutramine side-effects [23]. In a further small randomized trial of 46 obese adolescents, 81% in the sibutramine arm completed the 6-month trial, but none withdrew because of adverse events [24].…”
Section: Comparison With the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…2.1-2.8 kg over the course of 20 sessions) and there is a trend toward weight gain at follow-up. [13][14][15][16][17][18] While recent studies demonstrate promising results from sibutramine and behavior therapy with overweight adolescents, 19,20 there is continued need for innovative psychosocial interventions in this area.…”
Section: Introductionmentioning
confidence: 99%